La preservación de la memoria institucional de los proyectos universitarios a través del sistema de información de archivos abiertos (OAIS) - Viana, Gilberto Fladimar Rodrigues [UNESP]; Madio, Telma Campanha De Carvalho; Flores, Daniel (My University, 2014)
The preservation of the institutional memory of the Federal University of Santa Maria (UFSM), Brasil, consisting of those projects that have been considered as documentary heritage, is addressed. The details of these projects are stored in the database of the institution, called Information System for Education, in operation since 1992. Various theoretical and practical implications are analyzed, specially those of the concepts of institutional memory, database and digital media, and of the application of the NBR 15472 standard that specifies the open archives information system model (OAIS), with emphasis in its Section 4.
Preservation of the institutional memory of university projects using the open archival information system (OAIS)
Keywords: Academic archives; Brazil; Digital archives; Federal University of Santa María (Brazil); Institutional memory; OAIS